Gender roles of farmers on the production of African Black Beans (Akidi) in South-East, Nigeria - violet amarachukwu ohagwu; Esther Nnenna Chukwu; Onyeka Glory Onwubalili; Cynthia Eberechukwu Nwobodo; Remiguis Ikechukwu Ozioko; Onyinye Ifeanyi Nnadi (Journal of Agricultural Extension, 2024)
The study assessed gender roles on the production of African black bean (Akidi) in Southeast, Nigeria. It addressed the socio-economic characteristics of the respondents, their agronomic practices, gender roles in the production, constraints encountered by the respondents in the production practices of African black bean and possible strategies for improving the production practices of African black bean. Multi-stage sampling techniques was used to select 192 farmers used for the study. Descriptive statistics were used to analyze data. Results from the study show that the average age of female and male respondents were 43.58 and 41.20, respectively. Men, women and youths played complementary roles in various operations involved in African black bean production. Men (37.5%, 32.8%, 32.8% and 13.5%) and youths